An Alternative Method for the Obtention of Ceramic Foams from Gold and Silver Tailings with High Pyrite Content - Cristian Salazar (MDPI AG, 2021)
Mining extraction operations generate a large number of tailings that contain different mineral phases such as quartz (principally), complex silicates, metallic elements, etc. Tailings impose a serious concern as it is possible to have acid mine drainage potential, leaching, and percolation events of heavy metals into the environment under certain conditions. The objective of this work was to evaluate the technical feasibility of producing ceramic foams from gold and silver tailings with high sulfide gangue through a previous flotation process to eliminate impurities associated to this gangue, as it can produce SO2 in the foaming process, and to analyze the effect of the sintering time and the temperature on the characteristics of foams obtained with this type of waste. The results showed that the inverse flotation reduced the presence of impurities associated to sulfides. In addition, it was possible to observe that in the absence of a foaming agent, it was possible to obtain ceramic foams with an apparent density and a mechanical strength near to 1.0 g/cm3 and 0.5 MPa, respectively, when a higher sintering temperature and time were used. On the other hand, the presence of the foaming agent reduced the apparent density to 0.5 g/cm3 without decreasing to a great extent the mechanical strength of ceramic foams at lower sintering temperatures.